The effect of a shaken baby syndrome prevention program on Turkish mothers' awareness and knowledge: A randomized controlled study. Issue 2 (3rd February 2022) - Kaya, Ayla; Çelik, Derya; Efe, Emine
Abstract: Purpose: This study aimed to develop an evidence‐based education program to increase mothers' awareness and knowledge of shaken baby syndrome (SBS) and evaluate program effectiveness. Design and Methods: Mothers with babies between 2 and 4 months of age were completed the study (intervention group = 43 and control group = 44). This single‐blind randomized controlled study was conducted between September 2020 and February 2021. The intervention group participated in an 8‐week follow‐up. Outcome variables were assessed at baseline and 8 weeks after commencement of the intervention, which included measures to evaluate the administration of the shaken baby syndrome prevention program (SBSPP). The study was approved by ClinicalTrials.gov NCT04568538. Results: Scores for the SBS assessment survey were significantly higher in the intervention group than in the control group. Practice Implications: Developing effective interventions for SBS is an important public health goal. This study is the first to prove the effectiveness of an SBSPP conducted by nurses in Turkey. We believe that the implementation of this program in a larger sample will make a significant contribution to SBS reduction. Pediatric nurses identify the needs of parents with babies younger than 6 months and support them to manage this process correctly.